2018
DOI: 10.1051/shsconf/20185001171
|View full text |Cite
|
Sign up to set email alerts
|

Metaphorical Blends (Case Study of Metaphorization of Concept BOOK)

Abstract: The article deals with the mechanism of creating metaphor in the context of the theory of conceptual integration. A particular emphasis is laid on the basic theses of the theory of conceptual metaphor and the theory of conceptual integration. The comparison of G. Lakoff and M. Johnson’s theory of conceptual metaphor and G. Fauconnier and M. Turner’s theory of conceptual integration is carried out. The analysis of the examples of metaphorical mapping of the concept BOOK is conducted and three conceptual metapho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…Such blends may or may not be metaphorical in nature. However, there is a special type of conceptual blending: metaphorical blending which is especially pertinent to the present paper (Berberović & Mujagić, 2017;Berezhnykh, Sivtseva, Skopintseva, & Kontrimovich, 2018;Grady, 2005;Grady et al, 1999;Schröder, 2015;Semino, 2010). In metaphorical blends, metaphors serve as input spaces.…”
Section: Conceptual Integrationmentioning
confidence: 99%
“…Such blends may or may not be metaphorical in nature. However, there is a special type of conceptual blending: metaphorical blending which is especially pertinent to the present paper (Berberović & Mujagić, 2017;Berezhnykh, Sivtseva, Skopintseva, & Kontrimovich, 2018;Grady, 2005;Grady et al, 1999;Schröder, 2015;Semino, 2010). In metaphorical blends, metaphors serve as input spaces.…”
Section: Conceptual Integrationmentioning
confidence: 99%
“…There is a considerable corpus of linguistic research that has identified existing metaphors prevalent in American society. It must be underlined that metaphors are regarded as a means of expressing new knowledge being one of the means of linguistic creativity [4]. Cotrău, Cotoc, Happer, Philo, Hart, Tereškinas consider that the dominant group of metaphors representing immigrants as DISASTER, THREAT reveal negative stereotyping and show that negative representations are prevalent.…”
Section: The Analysis Of President Donald Trump's Political Languagementioning
confidence: 99%